1943
DOI: 10.1152/ajplegacy.1943.138.3.553
|View full text |Cite
|
Sign up to set email alerts
|

Observations Concerning the Origin of Renal Lymph

Abstract: The APS Journal Legacy Content is the corpus of 100 years of historical scientific research from the American Physiological Society research journals. This package goes back to the first issue of each of the APS journals including the American Journal of Physiology, first published in 1898. The full text scanned images of the printed pages are easily searchable. Downloads quickly in PDF format.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
9
0

Year Published

1957
1957
2023
2023

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(10 citation statements)
references
References 0 publications
1
9
0
Order By: Relevance
“…Our analysis of renal lymph confirms that of Sugarman et al (4) and Kaplan et d ( 5 ) with respect to its urea and sugar content: higher than plasma for urea and lower for sugar. But it differs from that of Sugarman et al in that we found the protein content of lymph to be quite constant at about 3.2 g % (Table 111).…”
supporting
confidence: 91%
See 1 more Smart Citation
“…Our analysis of renal lymph confirms that of Sugarman et al (4) and Kaplan et d ( 5 ) with respect to its urea and sugar content: higher than plasma for urea and lower for sugar. But it differs from that of Sugarman et al in that we found the protein content of lymph to be quite constant at about 3.2 g % (Table 111).…”
supporting
confidence: 91%
“…Its origin is unknown. But we have postulated that it comes from a large interstitial compartment ( 1,3), basing the hypothesis in part on the similarities in composition of "diluting fluid" and renal lymph as reported by Sugarman, Friedman, Barrett and Addis(4) and Kaplan, Friedman and Kruger (5). A more extensive analysis of the composition of the various fluids is reported here: arterial blood, venous blood, renal lymph, urine, and the kidney's distending fluids.…”
mentioning
confidence: 91%
“…We do not regard the presence of diatrizoate in renal nodes as evidence of leakage of tubular fluid. Intravenous inulin, which resembles diatrizoate in its mode of excretion in man [8] is also found in lymph draining from healthy kidneys and probably derives from renal cortical blood [19,20,23]. The absence of high concentrations of diatrizoate in renal lymph nodes in acute renal failure accords with diminished cortical blood flow [2,17].…”
Section: Discussionmentioning
confidence: 99%
“…One possibility is that the contribution to hilar lymph by tubular reabsorbate, distal to the tip of Henle's loop, is reduced during the decrease in distal reabsorption associated with furosemide. The conclusion that distal reabsorbate normally contributes to hilar lymph is based on the low lymph-plasma concentration ratio that has been found for glucose (8,25) Birtch et al (26), who found a redistribution of renal blood flow during furosemide diuresis. Although the precise relationship between blood flow and lymph production is not clear, a reduced output of lymph could result from a decrease in the medullary circulation of blood.…”
Section: Figurementioning
confidence: 99%